Optical properties of zinc lead tellurite glasses - Alazoumi, Salah Hassan; Aziz, Sidek Abdul; El-Mallawany, R.; Aliyu, Umar Sa'ad; Kamari, Halimah Mohamed; Zaid, Mohd Hafiz Mohd Mohd; Matori, Khamirul Amin; Ushah, Abdulbaset (Results in physics, 2018)
•Tellurite glass systems in the form of [ZnO]x [(TeO2)0.7-(PbO)0.3]1-x with x = 0.15, 0.17, 0.20, 0.22 and 0.25 mol% were prepared using the melt quenching technique.•FTIR and UV spectra were recorded at 280–4000 cm−1 and 200–800 nm, respectively.•XRD of the prepared samples have been measured for all samples.•The Optical energy band gap (Eopt), index of refraction (n) were calculated using absorption spectrum.•Molar polarizability, metallization criterion, polaron radius have been calculated for every glass composition. Tellurite glass systems in the form of [ZnO]x [(TeO2)0.7-(PbO)0.3]1-x with x = 0.15, 0.17, 0.20, 0.22 and 0.25 mol% were prepared using the melt quenching technique. XRD of the prepared samples have been measured for all samples. Both FTIR (280–4000 cm−1) and UV-Vis (200–800 nm) spectra have been measured. Optical band gap and refractive index were calculated for every glass sample. Density of glass, molar volume and oxygen packing density (OPD) were obtained. Values of the direct, indirect band gap ranged were found in the range 3.41–3.94 eV and 2.40–2.63 eV with increasing of ZnO concentration. Refractive index 2.58 and dielectric constant 6.66 were heigh at 17 ZnO mol% concentration. Molar polarizability, metallization criterion, polaron radius have been calculated for every glass composition.